Hubungan Self Efficacy Dengan Self Care Pada Pasien Penderita Diabates Melitus Tipe 2 Di Puskesmas Andalas - Lola Despitasari; Afrizal; Lenni Sastra; Fitria Alisa; Weny Amelia; Ria Desnita; Fadhila Annisa Afnel (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2022)
Self-efficacy is the patient's belief to be able to perform behaviors that support disease improvement. Self care is an action to help control blood sugar. Indonesia is a country that ranks 4th with type 2 DM sufferers. The highest prevalence of diabetes mellitus in Indonesia is in DKI Jakarta (3.4%). West Sumatera it self is a province with a prevalence of diabetes mellitus as much as 1.5%. Data on the prevalence of diabetes mellitus in the city of Padang with the highest case being Andalas Public Health Center. The design of this research is cross sectional. The sample is 73 respondents, the sampling technique is accidental sampling.The results showed that 39 respondents (53.4%) had good self-efficacy and 34 (46.6%). good self care as many as 54 (74.0%) and poor self care as many as 19 respondents (26.0%). Based on data analysis using the chi-square test, the p value = 0.004 (p 0.05), there is a relationship between self-efficacy and self-care in type 2 diabetes mellitus patients at the Andalas Health Center. The conclusion of this study is that there is a relationship between self-efficacy and self-care in patients with type 2 diabetes mellitus at the Andalas Health Center. It is suggested that nurses should always motivate patients to continue self-care in order to improve self-care in diabetes mellitus patients